2011
DOI: 10.1614/ipsm-d-10-00092.1
|View full text |Cite
|
Sign up to set email alerts
|

Does Superior Competitive Ability Explain Yellow Starthistle's (Centaurea solstitialis) Successful Invasion of Annual Grasslands in California?

Abstract: Yellow starthistle represents one of the most spectacular examples of biological invasion in the western United States. However, the mechanisms leading to its success have not been clearly elucidated. Although its success has been attributed to superior competitive ability, few competition studies have been performed with yellow starthistle to test this assertion. Yellow starthistle and wild oat (a dominant component of California annual grasslands) were grown in monocultures and mixtures to assess the strengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 54 publications
0
6
1
Order By: Relevance
“…Thus, PSF is likely unimportant in the invasion dynamics of these species. Cumulatively, this result combined with previous work suggest that the invasion of C. solstitialis is not consistently driven by PSFs and may be more related to species interactions and environmental conditions Spencer et al 2011;Young et al 2011). Previous research has investigated allelopathy for a congener (Centaurea stoebe or Centaurea maculosa) of our study species (Aschehoug et al 2014;Ridenour and Callaway 2001); however, no evidence of allelopathy has been found for C. solstitialis (Qin et al 2007) and we did not investigate any aspects of allelopathy in our study.…”
Section: Discussioncontrasting
confidence: 45%
“…Thus, PSF is likely unimportant in the invasion dynamics of these species. Cumulatively, this result combined with previous work suggest that the invasion of C. solstitialis is not consistently driven by PSFs and may be more related to species interactions and environmental conditions Spencer et al 2011;Young et al 2011). Previous research has investigated allelopathy for a congener (Centaurea stoebe or Centaurea maculosa) of our study species (Aschehoug et al 2014;Ridenour and Callaway 2001); however, no evidence of allelopathy has been found for C. solstitialis (Qin et al 2007) and we did not investigate any aspects of allelopathy in our study.…”
Section: Discussioncontrasting
confidence: 45%
“…), which may have improved its ability to recover following mowing damage. This supports our previous findings (Spencer et al ., ), where we reported that the deep root system for C. solstitialis was a mechanism to avoid intense competition with annual grasses, including Avena fatua L. Results suggest that C. solstitialis is able to compensate for defoliation because it has access to additional soil moisture. In more resource limiting environments, there would likely be a greater negative impact on seed production from the mowing or bud damage treatments.…”
Section: Discussionmentioning
confidence: 93%
“…We erected 12 PVC columns, 3 m high and 0.46 m in diameter, similar to those described previously (Spencer et al ., ). Columns were filled with c .…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Using glasshouse studies and climatic niche modelling based on principal components analysis, Dlugosch et al () found that YST in invaded areas has evolved a higher‐fitness life history at the expense of an increased dependence on water, resulting in larger plants and higher reproduction. Spencer et al () showed that intraspecific competition among YST plants exerts a greater influence on mean plant weight than does interspecific competition from exotic annual grasses because: (i) yellow starthistle depletes soil moisture to less than 5% to a depth of 270 cm compared with, for example, wild oats, which reduces soil moisture only to a depth of approximately 150 cm, and (ii) there is temporal separation of their phenology. Because soil moisture can be a limiting factor for YST in arid areas, a biophysical model (Ritchie, ) is used to compute the soil water balance of rainfall and run‐off above the holding capacity, as well as evapo‐transpiration from the plant and the soil surface (Gutierrez et al , ).…”
Section: Introductionmentioning
confidence: 99%